GPR174 mRNA Acts as a Novel Prognostic Biomarker for Patients With Sepsis via Regulating the Inflammatory Response - Wang, Jianli; Hu, Yanyan; Kuang, Zhongshu; Chen, Yao; Xing, Lingyu; Wei, Wei; Xue, Mingming; Mu, Sucheng; Tong, Chaoyang; Yang, Yilin; Song, Zhenju (Frontiers in Immunology, 2022)
Previous studies indicated that G-protein coupled receptor 174 (GPR174) is involved in the dysregulated immune response of sepsis, however, the clinical value and effects of GPR174 in septic patients are still unknown. This study is aimed to evaluate the potential value of GPR174 as a prognostic biomarker for sepsis and explore the pathological function of GPR174 in cecal ligation and puncture (CLP)-induced septic mice. In this prospective longitudinal study, the expressions of peripheral GPR174 mRNA were measured in 101 septic patients, 104 non-septic ICU controls, and 46 healthy volunteers at day1, 7 after ICU (Intensive Care Unit) admission, respectively. Then, the clinical values of GPR174 for the diagnosis, severity assessment, and prognosis of sepsis were analyzed. Moreover, the expressions of GPR174 mRNA in CLP-induced septic mice were detected, and Gpr174- knockout (KO) mice were used to explore its effects on inflammation. The results showed that the levels of GPR174 mRNA were significantly decreased in septic patients compared with non-septic ICU and healthy controls. And the expressions of GPR174 mRNA were correlated with the lymphocyte (Lym) counts, C-reactive protein (CRP), and APACHE II and SOFA scores. The levels of GPR174 mRNA at day 7 had a high AUC in predicting the death of sepsis (0.83). Furtherly, we divided the septic patients into the higher and lower GPR174 mRNA expression groups by the ROC cut-off point, and the lower group was significantly associated with poor survival rates (P = 0.00139). Similarly, the expressions of peripheral Gpr174 mRNA in CLP-induced septic mice were also significantly decreased, and recover after 72 h. Intriguingly, Gpr174-deficient could successfully improve the outcome with less multi-organ damage, which was mainly due to an increased level of IL-10, and decreased levels of IL-1β and TNF-α. Furtherly, RNA-seq showed that Gpr174 deficiency significantly induced a phenotypic shift toward multiple immune response pathways in septic mice. In summary, our results indicated that the expressions of GPR174 mRNA were associated with the severity of sepsis, suggesting that GPR174 could be a potential prognosis biomarker for sepsis. And GPR174 plays an important role in the development of sepsis by regulating the inflammatory response.